The effect of potassium dichromate on convoluted tubules of the kidney of adult male albino rats and the possible protective role of ginseng: a histological and immunohistochemical study. Issue 2 (June 2015) - El-Mahalaway, Abeer M.; Salem, Maysara M.; Mousa, Ayman M.
Abstract : Background: Chromium is a heavy metal used in painting, dyes, and leather tanning industries. Potassium dichromate Cr 6+ has demonstrated ability to induce nephrotoxicity associated with oxidative stress in humans and animals. Ginseng is one of the most popular herbal remedies, with a wide range of beneficial therapeutic effects. Objective: The aim of the study was to evaluate the effect of potassium dichromate on the convoluted tubules of adult male albino rats and the possible protective role of ginseng. Materials and methods: Forty adult male rats were divided equally into four groups (10 rats for each): Group I was the control group. In group II (the ginseng group), rats received a daily oral dose of ginseng at 100 mg/kg body weight/day by means of a gastric tube for 3 weeks. In group III (the potassium dichromate group), rats received a single subcutaneous injection of potassium dichromate at 15 mg/kg body weight. In group IV (the potassium dichromate and ginseng group), rats received potassium dichromate and ginseng for 3 weeks. Kidney specimens were prepared for light microscopic examination {stained with (H&E), Masson's trichrome, immunohistochemical detection of caspase-3}. Semithin and ultrathin sections were prepared for electron microscopic examination. Results: Group III showed degeneration and necrosis of cells of the renal tubules (proximal and distal) with tubular dilatation, an increase in collagen fibers around degenerated convoluted tubules, and cell apoptosis (highly expressed caspase-3). Electron microscopic results showed marked disrupted brush border of proximal convoluted tubules and disturbance of the basal infoldings of distal convoluted tubules. The cytoplasm had mitochondria that were irregular in shape and variable in size and large electron-dense particles. The smooth endoplasmic reticulum membrane revealed whorly appearance around the degenerated organelles. Group IV showed improvement in the light and electron microscopic changes described before. Conclusion: Ginseng has a protective effect against potassium dichromate-induced nephrotoxicity as it has antioxidant, anti-inflammatory, and antiapoptotic activities. We advice the workers who deal with chromium to take enough doses of ginseng to protect themselves from its side effects.